In vitro Direct Regeneration from Node and Leaf Explants of Phalaenopsis cv. Surabaya - Balilashaki, Khosro; Vahedi, Maryam; Karimi, Roghayeh (Plant Tissue Culture and Biotechnology, 2016)
An efficient and reproducible procedure for the direct regeneration of phalaenopsis cv. Surabaya using of nodal explants and leaf segments derived from in vitro flower stalk was conducted. Three experiments were carried out for shoot development and subsequent plant regeneration: Direct shoot regeneration from nodal explants of Phalaenopsis cv. Surabaya flower stalks on MS added with different combination of NAA and BAP, direct regeneration of protocormlike bodies (PLBs) from leaf explants in a MS with different concentrations of the TDZ, acclimatization of regenerated plantlets in different mixture of components and nutrients. The results showed that 5 mg/l BAP and 2 mg/l NAA were most effective concentration for shoot regeneration, regenerated shoots were cultured on half strength of MS containing activated charcoal, IAA and NAA at various concentrations, highest number of root (6.7) was obtained in higher concentration of NAA (2 mg/l). TDZ induced a higher frequency of embryogenesis from leaf explants than BAP, the highest number of embryos per explant was 22.45 at 3 mg/l TDZ. Altogether, BAP at higher concentration (10 mg/l) with 1 mg/l NAA had the highest enhancement on the amount of direct embryogenesis. In our investigation 87.20% plantlets via nodal explants survived acclimatization process in medium containing cocopeat and coal (1 : 1). The survival rate of regenerated plantlets via nodal explants (82.07%) was more than of regenerated plantlets via leaf explants (70.47). This protocol provides the basis for further investigation on micropropagation and breeding programs in Phalaenopsis cv. Surabaya. Plant Tissue Cult. & Biotech. 25(2): 193-205, 2015 (December)